(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This article has no abstract. The first 100 words appear below: A 60 year old lady from good socio-economic status was evaluated in the Emergency Department of the Addin Sakina Medical College, Jessore with moderately severe lower abdominal pain, marked anorexia, frequent vomiting, high fever with mild abdominal distension, constipation and burning sensation during micturition. The patient was well until 2 weeks before the presentation to the hospital when she develop-ed sudden onset of severe central abdominal pain associated with anorexia and vomiting. Short after, the pain shifted to the right iliac fossa. Later on, the fever developed which was continuous and not associated with chills and rigor. At the same time, she noticed that food aggravated the abdominal pain and discomfort.